CEO regulatory focus as the microfoundation of organizational ambidexterity: A configurational approach - David Pickernell (Journal of Business Research, 2021)
This study contributes to research on how microfoundations, in the form of CEO characteristics, influence ambidexterity (the capability to engage simultaneously in both exploration and exploitation) in SMEs. Specifically, it aims to identify which combinations of CEO regulatory foci (promotion and prevention focus) explain ambidexterity in SMEs and how these combinations themselves depend on situational conditions, namely market turbulence as perceived by the CEO and CEO tenure. Using data from 110 UK SMEs and fuzzy-set qualitative comparative analysis, we explore the combinations of CEO regulatory focus and situational conditions that lead to the presence and absence of ambidexterity. The findings contribute to a better understanding of SME ambidexterity and expand regulatory focus theory by showing that one of the regulatory foci tends to play a dominant role in shaping ambidexterity. The findings also reveal that situational conditions may compensate for the lack of promotion or prevention focus to produce ambidexterity.